IMPLEMENTASI PERATURAN BUPATI LEBAK NOMOR 1 TAHUN 2022 TENTANG TATA CARA PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI KELURAHAN MUARA CIUJUNG TIMUR KECAMATAN RANGKASBITUNG KABUPATEN LEBAK - Firman Saepudin; Nopi Andayani (LPPM STIA Banten, 2023)
Rural and Urban Land and Building Tax is a regional tax that is material in nature in the sense that the amount of tax payable is determined by the condition of the object, namely land or land and/or buildings. The problems in this study regarding the collection of Land and Building Taxes include: (1) The target for Rural and Urban Land and Building Taxes has not been achieved in Muara Ciujung Timur Village; (2) Lack of socialization regarding Rural and Urban Land and Building Tax in Muara Ciujung Timur Village; (3) The performance of the land tax collector and rural and urban buildings in Muara Ciujung Timur Village is less than optimal; (4) Lack of public awareness in the payment of Rural and Urban Land and Building Tax in Muara Ciujung Timur Village. The method used in this research is descriptive qualitative research method, the technique of determining the informants using purposive sampling technique, and data collection techniques observation and documentation. Based on the results of the study, it was found that the collection of Rural and Urban Land and Building Taxes had not run optimally. Suggestions from this research: conduct an evaluation, increase socialization that directly touches the community, should pay more attention and consider becoming a land and building tax collector in the village so that there are no more irregularities or mistakes.